Accumulation of perfluoroalkyl substances in human tissues - Pérez, Francisca; Nadal, Martí; Navarro-Ortega, Alícia; Fàbrega, Francesc; Domingo, José L.; Barceló, Damià; Farré, Marinella (Environment international, 2013)
Perfluoroalkyl substances (PFASs) are environmental pollutants with an important bioaccumulation potential. However, their metabolism and distribution in humans are not well studied. In this study, the concentrations of 21 PFASs were analyzed in 99 samples of autopsy tissues (brain, liver, lung, bone, and kidney) from subjects who had been living in Tarragona (Catalonia, Spain). The samples were analyzed by solvent extraction and online purification by turbulent flow and liquid chromatography coupled to tandem mass spectrometry. The occurrence of PFASs was confirmed in all human tissues. Although PFASs accumulation followed particular trends depending on the specific tissue, some similarities were found. In kidney and lung, perfluorobutanoic acid was the most frequent compound, and at highest concentrations (median values: 263 and 807ng/g in kidney and lung, respectively). In liver and brain, perfluorohexanoic acid showed the maximum levels (median: 68.3 and 141ng/g, respectively), while perfluorooctanoic acid was the most contributively in bone (median: 20.9ng/g). Lung tissues accumulated the highest concentration of PFASs. However, perfluorooctane sulfonic acid and perfluorooctanoic acid were more prevalent in liver and bone, respectively. To the best of our knowledge, the accumulation of different PFASs in samples of various human tissues from the same subjects is here reported for the very first time. The current results may be of high importance for the validation of physiologically based pharmacokinetic models, which are being developed for humans. However, further studies on the distribution of the same compounds in the human body are still required. •21 perfluoroalkyl substances were analyzed in 99 samples of human autopsy tissues.•The occurrence of perfluoroalkyl substances was confirmed in all human tissues.•Accumulation of PFASs followed particular trends depending on the specific tissue.•Lung was found to be the tissue accumulating a higher concentration of PFASs.